Outer membrane vesicles of Porphyromonas gingivalis trigger NLRP3 inflammasome and induce neuroinflammation, tau phosphorylation, and memory dysfunction in mice - Gong, Ting; Chen, Qi; Mao, Hongchen; Zhang, Yao; Ren, Huan; Xu, Mengmeng; Chen, Hong; Yang, Deqin (Frontiers in Cellular and Infection Microbiology, 2022)
Background Porphyromonas gingivalis (Pg), the keystone pathogen in chronic periodontitis, is reported to initiate Alzheimer’s disease pathologies in preclinical studies. However, the specific mechanisms and signaling pathways acting on the brain still need to be further explored. Outer membrane vesicles are derived from Gram-negative bacteria and contain many virulence factors of bacteria. We hypothesized that outer membrane vesicles are an important weapon of Porphyromonas gingivalis to initiate Alzheimer’s disease pathologies. Methods The outer membrane vesicles of Porphyromonas gingivalis (Pg OMVs, 4 mg/kg) or saline were delivered to 14-month-old mice by oral gavage every other day for eight weeks. Behavioral alterations were assessed by the open field test, Morris water maze, and Y-maze test. Blood–brain barrier permeability, neuroinflammation, tau phosphorylation, and NLRP3 inflammasome-related protein were analyzed. Results Pg OMVs impaired memory and learning ability of mice and decreased tight junction–related gene expression ZO-1, occludin, claudin-5, and occludin protein expression in the hippocampus. Pg OMVs could be detected in the hippocampus and cortex three days after oral gavage. Furthermore, Pg OMVs activated both astrocytes and microglia and elevated IL-1β, tau phosphorylation on the Thr231 site, and NLRP3 inflammasome–related protein expression in the hippocampus. In in vitro studies, Pg OMV (5 µg/ml) stimulation increased the mRNA and immunofluorescence of NLRP3 in BV2 microglia, which were significantly inhibited by the NLRP3 inhibitor MCC950. In contrast, the tau phosphorylation in N2a neurons was enhanced after treatment with conditioned media from Pg OMV-stimulated microglia, which was attenuated after pretreatment with MCC950. Conclusions These results indicate that Pg OMVs prompt memory dysfunction, neuroinflammation, and tau phosphorylation and trigger NLRP3 inflammasome in the brain of middle-aged mice. We propose that Pg OMVs play an important role in activating neuroinflammation in the AD-like pathology triggered by Porphyromonas gingivalis, and NLRP3 inflammasome activation is a possible mechanism.